Remittances and child labor in Bolivia - Michael Coon (IZA Journal of Migration, 2016)
This article explores the effect of remittances on the prevalence and intensity of child labor in Bolivia. Using household survey data, we find that children in remittance-receiving households are less likely to be actively supplying labor, and the number of hours worked per week declines with the size of remittances received. The size of the impact varies between urban and rural households. Remittances to urban households have a larger impact on moving children completely out of the labor force, but a smaller increase in remittance size is needed for an equal reduction in number of hours worked in rural areas.
Keywords: F24; O15; E26; 330; Remittances; Migration; Child labor; Bolivia